Proteasome Inhibitor Therapy for Waldenström's Macroglobulinemia - Dimopoulos, M.A.; Terpos, E.; Kastritis, E. (Clinical Lymphoma, Myeloma and Leukemia, 2013)
Proteasome inhibitors effectively kill tumor cells in myeloma and other plasma cell-related diseases. Preclinical data indicated that lymphoplasmatic cells are also vulnerable to proteasome inhibition and proteasome-targeting therapies have proved their clinical activity in Waldenström's macroglobulinemia (WM). Bortezomib is the first in class proteasome inhibitor (PI), and has been used in several clinical trials either alone or in combination with rituximab. Bortezomib treatment alone might induce major responses in 25%-60% of patients with WM but in combination with rituximab major responses might be as high as 50%-83%. Bortezomib might reduce immunoglobulin M levels rapidly and is not myelotoxic. However, peripheral neuropathy remains a major toxicity of bortezomib therapy; alternative schedules and dosing or route of administration (subcutaneous) might reduce neurotoxicity. Second generation PIs, such as carfilzomib, are also promising but further investigation is needed. © 2013 Elsevier Inc.
Keywords: Akt; bortezomib; Carfilzomib; mTOR; Proteasome